Hubungan Kepatuhan dan Kualitas Hidup Pasien HIV/AIDS di Kota Samarinda - Dewi Rahmawati; Jaka Fadraersada; Rani Oktavianir (Jurnal Sains dan Kesehatan, 2020)
Adherence to taking antiretroviral drugs is very important to prevent HIV replication in the body. Compliance with taking medication can improve the quality of life of HIV/AIDS patients. This study aims to determine the and quality of life HIV/AIDS patients and the relationship between adherence with the quality of life of HIV/AIDS patients in Samarinda City. The method used in this study was observational with prospectively used quantitative descriptive analysis to explain the adherence and quality of life of HIV/AIDS patients while for the relationship of adherence and quality of life of HIV/AIDS patients using non-parametric statistics with the wilcoxon test. The results showed that Compliance in HIV patients in Abdul Wahab Sjahranie Hospital are moderate compliance and in some puskesmas are low compliance. The quality of life of HIV/AIDS patients in Abdul Wahab Sjahranie Hospital are adequate quality of life and in some puskesmas the quality of life varies. The relationship of adherence with the quality of life of HIV/AIDS patients in Abdul Wahab Sjahranie Hospital and several puskesmas has a p ? 0,05 or can indicate no relationship between adherence with quality of life.